2017
DOI: 10.1021/acs.jpca.7b00722
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Experimental and Theoretical Rate Constants for the O(1D) + H2 Reaction

Abstract: In the present joint experimental and theoretical study, we report thermal rate constants for the O(D) + H reaction within the 50-300 K temperature range. Experimental kinetics measurements were performed using a continuous supersonic flow reactor coupled with pulsed laser photolysis for O(D) production and pulsed laser-induced fluorescence in the vacuum ultraviolet wavelength range (VUV LIF) for O(D) detection. Theoretical rate constants were obtained using the ring polymer molecular dynamics (RPMD) approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 72 publications
6
41
0
Order By: Relevance
“…22,36,37 This is also consistent with other barrierless reactions, such as the reaction between H 2 and C/O/S. 45,67 Though the rate coefficients for these reactions are less sensitive to temperature (within ≈ 10 −11 − 10 −12 cm 3 s −1 ) than the present reaction. At 50 K and above, the rate coefficient does not change significantly.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…22,36,37 This is also consistent with other barrierless reactions, such as the reaction between H 2 and C/O/S. 45,67 Though the rate coefficients for these reactions are less sensitive to temperature (within ≈ 10 −11 − 10 −12 cm 3 s −1 ) than the present reaction. At 50 K and above, the rate coefficient does not change significantly.…”
Section: Resultssupporting
confidence: 88%
“…The behavior of the recrossing factor with temperature T is similar to the ones observed previously for the reactions involving H 2 molecule with C 47 and O. 67 We know that the temperature dependence of κ(t) is related to the observed PMF profile. For instance, in the O + H 2 reaction, we observe a tiny barrier in the PMF profile calculated over the 67 As a result, the temperature dependence of the recrossing factor was the same, it increases from 0.30 at 300 K to 0.54 at 50 K. In contrast, the PMF profile of the first excited state (1 1 A ′′ state) has more sizable free energy barrier (up to ∼0.16 eV) along the reaction coordinate.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…On the theoretical side, the MPPST, SQM and RPMD methods were employed to describe the reaction dynamics over the 1 1 A 0 PES and to furnish thermal rate constants down to 50 K. RPMD calculations were also performed over the 1 1 A 00 PES. In a similar manner to our earlier investigation of the O( 1 D) + H 2 reaction, 16 these results confirm its negligible contribution to the overall reactivity at room temperature and below. To validate the theoretical approaches, rate constants were measured over the 50-296 K range using a supersonic flow reactor by following the kinetics of O( 1 D) loss.…”
Section: Introductionsupporting
confidence: 88%
“…The precise roles played by excited electronic states in different energy regimes are thought to be relevant considerations to distinguish the mechanisms governing the overall reaction dynamics. In a previous study of the O( 1 D) + H 2 reaction, 16 thermal rate constants derived by the RPMD method over the 1 1 A 0 and 1 1 A 00 PESs were shown to be in reasonably good agreement with measured values down to 50 K. As the 1 1 A 00 surface was shown to contribute negligibly to the overall reactivity below room temperature, these authors hypothesized that the difference between measurements and the RPMD results could be due to coupling between the 1 1 A 0 and 2 1 A 0 states. Indeed, precise QM wave packet (WP) calculations 44 of the O( 1 D) + H 2 system have suggested that this nonadiabatic pathway could contribute significantly to the overall reactivity.…”
Section: Introductionmentioning
confidence: 99%